2016
DOI: 10.1093/aobpla/plw085
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of tree invasions: complementing the unified framework for biological invasions

Abstract: Evolution greatly impacts the outcomes of biological invasions. In our review, we review such evolutionary processes, with an emphasis on tree invasions, and place them in the context of a unified framework for biological invasions. The processes and mechanisms described are pre-introduction evolutionary history, sampling effect, founder effect, genotype-by-environment interactions, admixture, hybridization, polyploidization, rapid evolution, epigenetics, and second-genomes. By understanding the mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 141 publications
(215 reference statements)
0
31
0
Order By: Relevance
“…Pre‐introduction evolutionary history, such as eco‐evolutionary experience, can play a major role in impacts of non‐native species during the acute phase of invasion (Zenni, Dickie, et al, ). For example, greater impacts are seen in regions where there are no native equivalents of the invading non‐native species (Davis, Callaway, et al, ).…”
Section: Context Dependencementioning
confidence: 99%
“…Pre‐introduction evolutionary history, such as eco‐evolutionary experience, can play a major role in impacts of non‐native species during the acute phase of invasion (Zenni, Dickie, et al, ). For example, greater impacts are seen in regions where there are no native equivalents of the invading non‐native species (Davis, Callaway, et al, ).…”
Section: Context Dependencementioning
confidence: 99%
“…It has been found that non-native populations are often characterized by reduced genetic diversity compared with native populations due to bottlenecks during introduction (Sakai et al 2001, Hirsch et al 2011). Despite this, rapid evolution of non-native species may occur even when experiencing bottleneck events (Dlugosch and Parker 2008; Schrieber and Lachmuth 2016; Zenni et al 2016a, b, this issue). Some studies, however, provide evidence that reduced genetic diversity is not always the rule for non-native populations, and that genetic diversity can be maintained by different mechanisms dependent on introduction history (multiple vs. single introductions), native range genetic structure and propagule pressure (Petit et al 2004; Prentis et al 2008; Le Roux et al 2011; Mandák et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only few consistent traits explaining invasion success of woody plants have been found (Moles et al 2012, Richardson et al 2014) which highlights the need for more detailed knowledge about factors contributing to the invasion success of trees or shrubs to predict and prevent further invasion processes. Trait dynamics of trees are particularly poorly understood in such species due to their long lifespans and generation times (Zenni et al 2016a,b, this issue). Here we focus on differences in post-germination traits between native and invasive populations of the Siberian Elm, Ulmus pumila (Ulmaceae).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of mutualists, such as mycorrhizal fungi, can contribute to the rapid establishment and spread of the non-native tree species (Dickie et al 2010; Zenni et al 2016) (Table 2). Here, the high EEE of the tree-host in the novel environment is directly influenced by the presence of the fungal mutualist.…”
Section: Fungal Associates and Tree Invasion Successmentioning
confidence: 99%
“…These so-called hitchhikers include those beneficial to their hosts, those detrimental, those that may become naturalized without causing harm, and those negatively impacting native plants via host shift events (Table 1). As discussed in this issue (Zenni et al 2016), the term “second genome”, recognising the impact of associated microbes on the phenotype of organisms, is also applicable to plant invasions, where success is due not only to plant traits, but also those of the associated microorganisms. Thus, hitchhikers, not only have the ability to promote the invasion success of their hosts in novel environments, but they potentially also threaten native ecosystem functioning through host-shifts.…”
Section: Introductionmentioning
confidence: 99%